2006
DOI: 10.1186/1746-4269-2-27
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomedicine in Himalaya: a case study from Dolpa, Humla, Jumla and Mustang districts of Nepal

Abstract: Traditional plant use in Nepal has been documented for millennia. The importance of plants as medicine has not diminished in any way in recent times, and traditional medicines are still the most important health care source for the vast majority of the population.This paper examines the ethnobotany and traditional use of plants extracted from the vulnerable alpine zone in the Dolpa, Humla, Jumla and Mustang districts of Nepal.The results of this ethnobotanical study indicate that a very large number of plant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
50
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(71 citation statements)
references
References 11 publications
11
50
0
1
Order By: Relevance
“…We have added 58 new medicinal plants, noted with asterisks (Additional File 1), in addition to the previous works of [13,44,47]. Many of these newly added plant species for Mustang are popular throughout Nepal and are used to treat a broad spectrum of ailments [12,15].…”
Section: Resultsmentioning
confidence: 99%
“…We have added 58 new medicinal plants, noted with asterisks (Additional File 1), in addition to the previous works of [13,44,47]. Many of these newly added plant species for Mustang are popular throughout Nepal and are used to treat a broad spectrum of ailments [12,15].…”
Section: Resultsmentioning
confidence: 99%
“…Traditional healers believe that roots are more effective than other plant parts. Studies elsewhere, have shown that the roots and other underground parts have high concentrations of bioactive compounds (Kunwar et al, 2006). Harvesting of roots for medicinal purposes is not sustainable, it threatens the survival of the majority of medicinal plants used in Nhema communal area.…”
Section: Plant Parts Usedmentioning
confidence: 99%
“…The use of plants in the treatment of several diseases is reported in different populations (e.g., Berg and Silva, 1988;Bird, 1991;Verger, 1995;Guarim-Neto, 2006;Kunwar et al, 2006). The knowledge of medicinal plants often represents the only therapeutic option for many communities and ethnic groups.…”
Section: Introductionmentioning
confidence: 99%